Photocatalytic degradation of paraquat dichloride over ceo2-modified tio2 nanotubes and the optimization of parameters by response surface methodology - Eleburuike, Naimat Abimbola (Royal Society of Chemistry (RSC), 2016)
Decontamination of water sources by one-dimensional (1D) nanostructured TiO 2 holds great potential due to their unique electronic and textural properties. In this study, CeO 2 -modi fi ed TiO 2 nanotubes (Ce – TNTs) have been prepared by impregnation of CeO 2 on hydrothermally synthesized TiO 2 nanotubes (TNTs). The catalysts were characterized by XRD, HRTEM, EDX, STEM, EELS, DR-UV/VIS spectroscopy and nitrogen adsorption (NA) analyses. The photocatalytic activities of the synthesized Ce – TNTs were examined on the degradation of paraquat dichloride (PQ) under UV light. The modi fi cation of TNTs with CeO 2 led to an enhancement of the photocatalytic activity. Box – Behnken design (BBD) based on response surface methodology (RSM) was used to optimize three experimental parameters namely; CeO 2 ratio, calcination temperature and catalyst loading. ANOVA of the generated quadratic model yielded a coe ffi cient of determination, R 2 of 0.9926 and probability, P < 0.0001, which con fi rms that the model is suitable for predicting the optimum degradation e ffi ciency of PQ. Based on this model, the calcination temperature and CeO 2 ratio were the most signi fi cant parameters and the interactions between these parameters and the catalyst loading were also signi fi cant. The predicted optimum conditions that would give a maximum of 80.798% degradation of PQ in 4 h were 9.01% CeO 2 ratio, 760.49C calcination temperature and 0.38 g catalyst loading. Validation experiments were conducted in triplicate and an average of 80.27% degradation of PQ was achieved which is in agreement with 80.798% predicted. Under these optimum conditions, TOC analysis showed that 51.10% mineralization of PQ was achieved within 4 h. Therefore, this work further con fi rms that the photocatalytic treatment of organics-contaminated water can be designed and optimized by RSM.